2018
DOI: 10.2196/resprot.8794
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Psychiatric Comorbidity in Immune-Mediated Inflammatory Disease: Protocol for a Prospective Study

Abstract: BackgroundImmune-mediated inflammatory diseases (IMID), such as inflammatory bowel disease (IBD), multiple sclerosis (MS), and rheumatoid arthritis (RA), are highly prevalent in Canada and the United States and result in substantial personal and societal burden. The prevalence of psychiatric comorbidities, primarily depression and anxiety, in IMID exceeds those in the general population by two- to threefold, but remains underdiagnosed and undertreated. Furthermore, the effects of psychiatric comorbidity on IMI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 103 publications
(84 reference statements)
0
85
0
Order By: Relevance
“…The sample size for the present study was determined based on a power analysis for the two principal longitudinal study objectives. Details of the sample size calculation and comprehensive protocol information is available elsewhere [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sample size for the present study was determined based on a power analysis for the two principal longitudinal study objectives. Details of the sample size calculation and comprehensive protocol information is available elsewhere [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The source population was participants in a longitudinal study of the effects of psychiatric comorbidity on immune-mediated inflammatory diseases (the 'IMID' study) that recruited 255 persons with definite MS (Polman et al, 2011) from the province-wide Winnipeg MS Clinic (Marrie et al, 2018). The present study enrolled a subgroup of 111 IMID study participants aged ≥18 years, with adequate knowledge of the English language who underwent a study visit between September 2016 and July 2017.…”
Section: Participantsmentioning
confidence: 99%
“…As described in detail elsewhere (Marrie et al, 2018), participants completed questionnaires, and underwent standardized clinical assessments conducted by trained personnel.…”
Section: Participantsmentioning
confidence: 99%
“…As part of a larger cohort study assessing psychiatric comorbidities in patients with chronic immune-inflammatory diseases (Marrie et al, 2018), we recruited 255 participants with neurologist-confirmed diagnoses of MS (Poser et al, 1983;McDonald et al, 2001;Polman et al, 2005;Polman et al, 2011), from the Winnipeg MS Clinic, the only clinic specializing in MS care in the province of Manitoba, Canada. Recruitment took place by telephone, mail or in clinic.…”
Section: Study Populationmentioning
confidence: 99%
“…Recruitment took place by telephone, mail or in clinic. All participants were aged 18 years and older, residing in Manitoba, able to provide informed consent and willing to participate in the cohort study for three years (Marrie et al, 2018). Ethics approval was obtained from the University of Manitoba Health Research Ethics Board.…”
Section: Study Populationmentioning
confidence: 99%